FUNCTIONAL OUTCOME OF PATIENTS WITH MODERATE-TO-SEVERE OSTEOARTHRITIS TREATED BY TOTAL KNEE ARTHROPLASTY AT A TERTIARY CARE CENTER - Patil, Jaydeep; Ghorpade, Kapil; Khambalkar, Shouryashil; Naik, Nagesh; Patil, Tanish (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Osteoarthritis (OA) is one of the common causes of significant morbidity in elderly individuals. It typically manifests as painful joints affecting mobility in individuals particularly women in and after fifth or sixth decade of life. While most of the mild-to-moderate cases are managed conservatively, in severe OA total knee arthroplasty (TKA) is being increasingly done with good functional outcome. The aim of the study was to assess functional outcome in case knee OA cases treated by TKA. The study aimed to study the complication in patients undergoing TKA. Methods: Forty patients with moderate-to-severe knee OA and treated by TKA were included in this study on the basis of a predefined inclusion and exclusion criteria. Demographic details such as gender and age were noted in all the cases. Body mass index (BMI) was determined. All patients were treated by TKA. Functional outcome was assessed by Japanese Orthopaedic Association score (JOA) as well as Functional knee clinical score (KCS). Incidence of complications was assessed during follow-up. For statistical purposes, p<0.05 was taken as significant. Results: There were 25 (62.50%) females and 15 (37.50%) males with a M: F ratio of 1:1.66. 13 (32.50%) patients were obese (BMI≥30) and 16 (40.00%) patients were overweight (BMI≥25 but <30). A total of 11 (27.50%) patients had BMI <25. The mean KCS as well as JOA scores at the time of final follow-up were found to be significantly improved as compared to KCS and JOA scores at the time of presentation and the difference was found to be statistically highly significant (p<0.05). There was a significant reduction in pain as assessed by VAS score. Total 6 (15%) patients developed complication which could be managed conservatively. Conclusion: TKA in patients with moderate-to-severe OA treated by TKA is associated with significant improvement in functional outcome and acceptable complication rate.